Exploitation of heterosis for growth related traits in African marigold (Tagetes erecta) - PANWAR, SAPNA; SINGH, KANWAR PAL; JANAKIRAM, T; BHARADWAJ, C; NAMITA, NAMITA (The Indian Journal of Agricultural Sciences, 2026)
A line × tester set of 15 parents involving three male sterile lines and 12 pollen parents of (Tagetes erecta L.) African marigold and their 36 hybrids were analyzed for heterosis with respect to various growth related traits. The hybrids MS 8 × Af.Sel.11, MS-5 × Af.Sel.16 and MS 8 × Af.Sel.11 exhibited maximum heterosis over better parent, mid parent and commercial check respectively for plant height. The maximium heterosis value for low plant spread were observed in the hybrid MS 7 × Af.Sel.1 over better, mid and commercial check, respectively, however hybrids (MS 5 × Af.Sel.10), MS 5 × Af.Sel.14 and MS 7 × Af.Sel.10 reported highest values of heterosis for stalk length over better, mid and commercial check respectively. The hybrids (MS 7 × Af.Sel.5, MS 5 × Pusa Narangi Gainda and MS 5 × Pusa Narangi Gainda exhibited maximum heterosis for stem diameter over better, mid and commercial check, respectively. For number of primary branches, the maximum heterosis over better, mid and commercial check were observed in hybrids MS 7 × Af.Sel.14, MS 7 × Af.Sel.14 and MS 7 × Af.Sel.12 respectively. The hybrids MS 7 × Af.Sel.11, MS 8 × Af.Sel.12 and MS5 × Pusa Narangi Gainda exhibited highest heterosis for number of secondary branches over better, mid and commercial check, respectively.